Analisis Yuridis terhadap Pelampauan Kewenangan Notaris dalam Pembuatan Akta Autentik Berdasarkan Undang-Undang Jabatan Notaris Nomor 2 Tahun 2014 - Husnul Khulqiyah; Gufran; Zuhrah (Jurnal Hukum Lex Generalis, 2026)
This study examines the limits of a notary’s authority in the preparation of authentic deeds based on the provisions of Law No. 2 of 2014 Amending Law No. 30 of 2004 on the Office of the Notary and analyzes the legal consequences that arise if such authority is exercised beyond the established provisions. This study employs a normative legal research method using a statutory approach and a conceptual approach. The findings indicate that a Notary’s authority in the preparation of authentic deeds constitutes an attributive authority directly granted by law and its exercise must adhere to the established boundaries. Exceeding a notary’s authority can occur in three forms: exceeding authority in terms of subject matter, territorial scope and procedural violations. Such actions have the potential to affect the validity of the deed, thereby reducing its probative value or even causing it to lose its authentic nature.